Market models and segregation: examining mechanisms of student sorting. Issue 1 (2nd January 2022) - Lubienski, Christopher; Perry, Laura B.; Kim, Jina; Canbolat, Yusuf
ABSTRACT: In recent decades, policymakers around the globe have adopted market mechanisms such as consumer-style choice, provider autonomy and competition. Such policies may improve educational equity since families can choose options outside of their assigned local school. Yet research from multiple countries is finding a link between greater use of such policies and increases in social segregation in schooling. This comprehensive analysis is a first step in examining the specific policies and institutional and contextual factors that may alleviate or exacerbate different types of student sorting. Rather than focus only on the question of causation, we instead examine the potential pathways through which market mechanisms might impact student sorting, and highlight the role of incentives in shaping these pathways. In specifying several such pathways, we then present a framework through which further research might conceptualize and theorize the relationship between market mechanisms and student opportunity.